THE IMAGE MAINTENANCE OF PURWAKARTA REGENT THROUGH GEMPUNGAN ACTIVITIES IN PURWAKARTA REGENCY - Herladiati, Anggita; Damayanto, Trie; Prastowo, FX. Ari Agung (Prodi Teknologi Pendidikan, 2016)
Abstrack, Gempungan is an implementation of Purwakartagovernment program contained in